(untitled) (Biological Sciences - PJSIR, 2009)
Molecular weight of bacteriocin like substance (BLIS) of a new strain of Bacillus lentus 121 was found to be approximately 11 kDa. Purification of BLIS was attained by single step gel exclusion chromatography. BLIS was characterized by studying the inhibitory spectrum. It was active at broad pH range, high temperature and high NaCl concentration and showed sensitivity to proteolytic enzymes like trypsin, a-chymotrypsin and papain, the characters desirable for food preservation. BLIS extended the shelf stability of milk upto 21 days as a biopreservative.